Isolation of Bacillus strains inhibition disease resistance of Acute Hepatopancreatic Necrosis Disease on the Shrimp in Can Gio, Vietnam. Issue 6 (January 2020) - Phung, L T; Phuong, T T M; Phung, N K; Nicolas, M
Abstract: Recently, the outbreak and severe damage to the shrimp farming industry is Early Mortality Syndrome (EMS) or Acute Hepatopancreatic Necrosis Disease (AHPND). The selection of Bacillus strains inhibition disease resistance of the acute hepatopancreatic necrosis disease on the shrimp is a research filed that is much attention due to Bacillus subtilis is a group of beneficial bacteria that presents in the majority of biological products for aquaculture, especially for shrimp. Competitiveness of Bacillus subtilis towards the harmful bacteria firstly is the number of bacterial cells. Beside, Bacillus has capacity to create a large amount of extracellular enzymes aid digestion, antibiotics or the inhibitor has the characteristic for resistance to the strains of Vibrio Parahaemolyticus. In this work, the inhibition ability of the Bacillus strains for the AHPND on the brackish water shrimp is studied. In which, the Bacreria is isolated and filtered from shrimp farm in Can Gio province that contain the characteristic of antagonizing Vibrio parahaemolyticus, which cause AHPND on shrimp in laboratory conditions. The results show that Bacillus subtilis produced 2, 5 – Diketopiperazines capable to inbihite the growth of pandemic strain of Vibrio parahaemolyticus in Landy media for hightest activity was 200 AU/mL after 24 h of culture. This research is create the possibility of using probiotics to control the pantogenic clones Vibrio parahaemolyticus that cause AHPND for brackish water shrimp farming in Can Gio province as well as other areas in Vietnam.